Impact of Message Losses on Push-Sum Protocol in Chosen Topologies - Kenyeres, Martin; Kenyeres, Jozef; Novotny, Bohumil (European Scientific Journal, ESJ, 2017)
In this paper, we examine the natural robustness of the push-sum protocol to message losses in a tree, a star, a mesh, a ring and a link topology. We experimentally verify the impact of this failure on the character of the estimations, the deviation of the final estimation from the real value and the impact on the change of the convergence rate.